(untitled) (Jurnal Bahasa, 2006)
Karyamin, the main figure from short story Senyum Karyamin (The Smile of Karyamin), was a poor stone collecting coolie. He did not talk much, except smiling. His smiling expressed many kind of emo-tions and states of mind, such as happy, disgust, insult, sad, alert, to agree with and sympathy. Different meaning of emotions and states of mind depend entirely on the situation in which an emotion word ap-peared from the text. The word smile could express different emotions or states of mind from different context. Beside senyum and its deriva-tion such as tersenyum, tersenyum-senyum and senyuman, other words expressing emotions and states of mind were also analysed, The promi-nent emotion from Karyamin was his dissatisfaction toward his poor life. But, he could use his mind when a government official asked him for money to help the poorer in Africa. He did not manifest his angry by fighting or scolding him, except smiling or laughing. But, it did not mean that Karyamin and his friends-who had the same fate as him-always sad. They knew how to make jokes. Sometimes they made their friends as the victim of their jokes, sometimes they laughed at their own stupidness, or found something that could make them laughing. Although they were very poor and worked hard to earn some money, their life was fulfilled with jokes. The solidarity among them was very strong. They took sympathy toward others difficulty or sadness. On the contrary, the government official was described as a man who was easy to get angry, did not have humorous sense and pitiness.